Project Profile: Trust Systems for Regional Healthcare - Andrew Matthews (Healthcare Quarterly, 2007)
In every healthcare setting, there is an expectation of privacy and security. Patients expect their records to be confidential, and the healthcare provider is responsible for ensuring that this is the case. Until recently, this has not been an issue as records have been paper based and kept in files under lock and key. But with the move toward creating standard electronic health records that can be shared across multiple institutions and by greater numbers of healthcare professionals, the potential for a privacy breach increases exponentially.
Keywords: electronic health record, Regional Healthcare, privacy and confidentiality, hospital security